Isolation and identification on microorganism decomposers of Palu local cow manure of Central Sulawesi, Indonesia - I Idham; S Sudiarso; N Aini; Y Nuraini (Journal of Degraded and Mining Lands Management, 2016)
Microbial decomposers are living things posessing an important role in outlining materials derived from organic compounds entering the environment as plant nutrients so that they arereusable by the greenery. This study was aimed to isolate and identify types of microbial decomposers from Palu local cow manure of Central Sulawesi, Indonesia. The results showed that in Palu local cow manure there were three types of microbial decomposers namely Lactobacillus sp, Actinomycetessp and Aspergillus sp. In Actinomycetes sp., the colony growth was very slow and firmly attached to the media surface after incubated for 7 days. It showed formation of mycelium spreading on the media surface with a serrated edge. Aspergillus sp.had morphological characteristics formed on media as follows: green-yellowcolonies; like-furtextures; green conidia; radiatconidia arrangement, uniseriat, fialidwhich almostfilled the entiresurface of vesicles; like-ballroundvesicle; coarse, thick-walled, and dark greenconidiophores.